NUTRITIONAL STATUS, ENERGY INTAKE AND CALORIE DRINKS AMONG INDONESIA ADOLESCENTS: A CROSS-SECTIONAL STUDY - Yulyani, Wilda Siti; Safitri, Debby Endayani (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: Adolescents often experience an imbalance between intake and energy expenditure, resulting in the problem of excess nutrition. Unbalanced energy intake and expenditure and lack of nutritional knowledge are the main factors causing over nutrition. The results of research on National Ministry data showed that the nutritional status of adolescents aged 12-18 years who were over-nourished was 19.1% and obesity was 31%. However, the nutritional status of over-nutrition at the provincial level in Banten was 20.9% and obesity was 30%. Purpose: The purpose of this study is to determine the relationship between energy intake, macronutrients, calorie drinks and nutritional knowledge on the nutritional status of adolescents aged 15-18 years in Sukabakti Sub district, Tangerang Regency. Methods: Sample was taken by using Proportional Random Sampling technique as many as 97 samples. The variables studied were energy intake, macronutrients, calorie drinks and nutritional knowledge on adolescent nutritional status. This type of research used quantitative research with Chi-Square analysis test. Results: In this study, there was no significant (P > 0.05) between energy intake (P = 0.827), protein intake (P = 468), fat intake (P = 0.849), carbohydrate intake (P = 0.449), calorie drinks (P = 0.227), and no relationship between nutritional knowledge and nutritional status (P = 0.231). Conclusion: Since adolescent nutritional status is influenced by several factors. not only intake and knowledge, but also influenced by physical activity, infectious diseases, attitudes, parents, environment and many more.